Recurrent gigantic pyogenic granuloma disturbing speech and mastication: a case report and literature review. - Ong, M.A.; Chai, W.L.; Ngeow, Wei Cheong (1998)
A case of gigantic pyogenic granuloma with three recurrences in the lower anterior gingiva is presented. Surgical wide excision of the lesion is the treatment of choice. The tumour must be excised down to the periosteum and the irritants around it removed to avoid recurrence. A contributing factor to the gigantic lesion is hormonal changes during pregnancy. Long-term review for 18 months after the third surgery showed no evidence of recurrence at the surgical site.